Development of a fast readout system for the DISC DIRC prototype of PANDA - Köseoğlu-Sarı, İlknur; Justus Liebig University Giessen (My University, 2021)
PANDA is one of the four major experiments at the future Facility for Antiproton and Ion Research (FAIR) in Darmstadt, Germany. The physics goal of PANDA is to better understand unknown phenomena in the non-perturbative QCD region, the structure of hadrons including the strong and weak forces. The program of PANDA is planned to be studied at different momenta of the antiproton beam during collisions with a fixed proton target. After the antiproton-proton annihilation, all possible decay products are to be detected using a hermetic 4π detector. The PANDA detector is designed as double spectrometer. The forward spectrometer utilizes several subdetectors including a dipole magnet. The target spectrometer is designed in the form of an onion shell structure with a combination of compact subdetectors such as a calorimeter, a tracking system with magnets and muon identification. Since a classical hadronic calorimeter is missing, charged hadrons are discriminated by two DIRC (Detection of Internally Reflected Cherenkov light) in a barrel and disc shape to cover the polar angle range from 5 ◦ to 140 ◦ . The world’s first disc-shaped detector Endcap Disc DIRC (EDD) is a part of particle identification of the PANDA system to cover the polar angle range 5 ◦ to 22 ◦ . The separation power of charged pions and kaons is aimed to have 3 standard deviations up to 4 GeV/c momentum. When these charged particles traverse the fused-silica radiator of the EDD, Cherenkov photons are emitted and reflected internally to the readout system, thereby carrying the angle information of the charged particle. The hit pattern of Cherenkov photons will be detected via highly granulated Microchannel-plate photomultiplier tubes (MCP-PMTs), and the analog signals of the MCP-PMT anode pins will be digitized by a readout system. This thesis focuses on a development of a fast readout system of the EDD to achieve the specified performance. The readout system of the EDD consists of the ASIC based TOFPET2 system which was designed by the PETsys company for PET applications. In order to improve the readout electronics for our purposes, deficiencies of the existing system were determined in different steps such as test beam experiments at CERN in 2018. The ASICs from 2018 production batch were further improved in an experimental test setup called Giessen Cosmic Station (GCS). The GCS was built in the University of Giessen to use the cosmic muons with a selection of 600 MeV minimum energy as a generator of Cherenkov photons. It consists of scintillator bars to reconstruct the track of the cosmic muons. The GCS was continuously enhanced by designing a light-tight cases for optical elements, and by changing the air-cooling into more stable liquid cooling for electronics. A full-sized EDD quadrant was integrated into the GCS setup. By using optimized ASICs, data was acquired with a triggerless system similar to the one used in PANDA. Data analysis confirmed by Monte Carlo (MC) shows the expected detection performance of the readout system. The custom PCB which will be used for the final EDD in PANDA was designed in a tight collaboration with PETsys company by implementing only the required electronic elements and removing the ones related to SiPM applications. Thereby radiation hardness, communication with the PANDA central DAQ system, and compatibility to the imagnetic field had to be newly considered. In addition to that, the readout system of the final EDD has to fit into a compact space. This limits the possible positions of the electronic elements with different dimensions. Regarding all spatial constraints, one design was chosen out of three different suggested designs considering the number of readout modules in the available space. One of the critical issues is keeping temperature of the electronics in a compact PCB around 20 ◦ . For that, a permanently running liquid cooling system was designed. After the production of the custom design PCB, a light-tight experimental setup was prepared for testing purposes with permanent magnets depending on test purposes. The readout system with the presented designs and implementations reached a powerful state that allows for pursuing the next phases of the PANDA project.
Keywords: Cherenkov detectors; particle identification; cosmic station; ddc:530